Doing Business in India 2009 - World Bank; International Finance Corporation (World Bank, Washington, DC, 2017)
Doing business in India 2009 is the first country specific subnational report of the doing business series that measures business regulations and their enforcement across India. Doing business in India 2009 covers 10 out of the 12 previously measured cities, and documents their progress. It adds 7 new locations, expanding the study to 17 locations. Comparisons with the rest of the world are based on the indicators in doing business 2009. The indicators in doing business in India 2009 are also comparable with the data in other subnational and regional doing business reports. The indicators are used to analyze economic outcomes and identify what reforms have worked, where, and why. Other areas that significantly affect business, such as a country's proximity to markets, the quality of infrastructure services (other than services related to the trading across borders indicator), the security of property from theft and looting, the transparency of government procurement, macroeconomic conditions, or the underlying strength of institutions, are not directly studied by doing business.